Water Birth as Neuroendocrine Medicine: A Critical and Integrative Review of Hormonal and Psychophysiological Impacts on Maternal and Neonatal Outcomes - Sanjaya, I Nyoman Hariyasa; Andonotopo, Wiku; Dewantiningrum, Julian; Pramono, Mochammad Besari Adi; Mulyana, Ryan Saktika; Pangkahila, Evert Solomon; Akbar, Muhammad Ilham Aldika; Yeni, Cut Meurah; Aldiansyah, Dudy; Bernolian, Nuswil; Wiradnyana, Anak Agung Gede Putra; Darmawan, Ernawati; Stanojevic, Milan; Kurjak, Asim (The Indonesian Society of Perinatology, South Jakarta, Indonesia, 2025)
Background: Water birth, defined as labor and/or delivery conducted in warm water, has gained increasing recognition as a patient-centered and physiologically supportive birth practice. Beyond analgesia, growing evidence indicates that water immersion during labor modulates maternal neuroendocrine regulation, psychological well-being, and neonatal physiological adaptation. Nevertheless, these hormonal and psychophysiological mechanisms remain insufficiently integrated into conventional perinatal research and clinical frameworks. This review aims to synthesize current evidence on the neuroendocrine, psychophysiological, obstetric, and neonatal effects of water birth and to evaluate its clinical effectiveness and safety in low-risk pregnancies. Methods: An integrative review was conducted using a PRISMA-guided approach to identify peer-reviewed studies published between 2000 and 2025. Literature searches retrieved 3,287 records from major biomedical databases, of which 44 studies (12 randomized controlled trials, 19 cohort studies, 6 case–control studies, and 7 systematic reviews) met inclusion criteria. Data were synthesized thematically, focusing on maternal hormonal responses (oxytocin, β-endorphins, cortisol, prolactin), labor outcomes, breastfeeding, postpartum mood, neonatal adaptation, and safety considerations. Results: Across study designs, water immersion during labor was associated with increased endogenous oxytocin and β-endorphin activity and reduced stress-related hormonal responses. Clinically, first-stage labor was shortened by approximately 42–78 minutes, and epidural analgesia use was reduced by 30–50% compared with conventional land birth. Episiotomy rates were generally below 5%, and maternal satisfaction scores were consistently higher. Early breastfeeding initiation occurred in 86–92% of water birth cases, with exclusive breastfeeding rates at six weeks ranging from 66–77%. Neonatal outcomes, including 5-minute Apgar scores and NICU admission rates, were comparable to or slightly better than conventional birth in low-risk populations, with no consistent increase in infection or respiratory complications when standardized protocols were applied. Conclusion: Water birth supports a hormonally optimized and psychologically protective labor environment, with measurable benefits for labor efficiency, maternal experience, breastfeeding success, and neonatal physiological transition. When implemented under evidence-based guidelines, it represents a credible non-pharmacological option within contemporary, physiology-informed maternity care.